Trends in the incidence and prevalence of atrial fibrillation in Iceland and future projections - Stefansdottir, Hrafnhildur; Aspelund, Thor; Gudnason, Vilmundur; Arnar, David O. (Europace (London, England), 2011)
Aims Data are scarce on the epidemiology of atrial fibrillation (AF) in Europe. The aim of this study was to examine recent trends in the incidence and prevalence of AF and project the prevalence to the year 2050. Methods and results From 1991 to 2008 a total of 4905 residents of Reykjavik, Iceland were diagnosed with AF at the city's main health care centre. The age-standardized incidence of AF increased in women (0.9% per year, 95% CI 0.1-1.8) but not in men (0.1% per year, 95% CI −0.6 to 0.9). The age-standardized prevalence increased per year by 1.8% (95% CI 1.3-2.3) in men and 2.3% (95% CI 1.7-2.9) in women from 1998 to 2008. The number of adults with AF in Iceland is projected to increase from 4495 (prevalence 2.0%) in 2008 to 11 088 (prevalence 3.5%) in 2050, if the incidence of AF and mortality remain constant beyond 2008. However, if the incidence continues to increase as it has and mortality decreases according to projections for the general population, the projected number will rise to 13 583 (prevalence 4.3%). Conclusion In this study in a northern European population, the incidence of AF increased in women but not men from 1991 to 2008. The prevalence of AF is currently high and the number of patients with AF is expected to triple in the next four decades. AF is already a serious public health problem and the burden of this disease could reach epidemic proportions in the coming years.